2019
DOI: 10.3390/medicina55080486
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Serum Concentrations of Pro- and Anti-Inflammatory Cytokines and Nutritional Status in Patients with Traumatic Head Injury in the Intensive Care Unit

Abstract: Background and objective: The aim of the present study was to examine the relationship between serum levels of pro-inflammatory cytokines (IL-6, IL-1β, and TNF-α) and anti-inflammatory cytokines (IL-10) measured once at the baseline with changes in nutritional status of patients with traumatic head injury (THI) assessed at three consecutive times (24 h after admission, day 6 and day 13) during hospital stay in the intensive care unit (ICU). Materials and Methods: Sixty-four patients with THI were recruited for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Some of those biomarkers correlated with Glasgow Outcome Score at 6-month and with mortality in TBI patients [46]. Some authors have also shown that inflammatory cytokines are sensitive in the prognosis of post-TBI recovery and significantly correlated with 6-month outcome [47,49]. Noteworthy, the severity of TBI is commonly assessed by CT examinations, which cannot provide any information about the metabolic and inflammatory response after brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Some of those biomarkers correlated with Glasgow Outcome Score at 6-month and with mortality in TBI patients [46]. Some authors have also shown that inflammatory cytokines are sensitive in the prognosis of post-TBI recovery and significantly correlated with 6-month outcome [47,49]. Noteworthy, the severity of TBI is commonly assessed by CT examinations, which cannot provide any information about the metabolic and inflammatory response after brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the time course of patients' nutritional condition after SCI has not been reported previously, although some studies have reported nutritional findings for different forms of trauma 14 . For example, in a study evaluating patients hospitalized in the intensive care unit with a traumatic head injury, nutritional parameters significantly reduced from hospital admission to hospitalization days 7 and 13 14 . Our study demonstrated that nutritional status deteriorated until 1 month after injury; however, it gradually improved until 3 months after injury.…”
Section: Discussionmentioning
confidence: 93%
“…In general, the results of studies on the administration of high-protein diets in patients to the ICU are very controversial (20). Some observational studies have shown bene cial effects of high protein intake with clinical outcomes, while these bene ts have not been fully con rmed in clinical trial studies, however, few studies have found that very early protein intake is even harmful (21)(22)(23)(24)(25)(26). A retrospective showed that low protein intake (<0.8 g/kg/day) in the rst 3 days of ICU admission along with high protein intake ((>0.8 g/kg/day)) after the third day of admission was associated with a reduction in 6-month mortality, in addition, low protein intake throughout the all ICU stay was associated with worst clinical outcomes (27).…”
Section: Discussionmentioning
confidence: 99%